Isopiestic measurements and thermodynamic model for the ternary system Li2B4O5(OH)4) + LiB5O6(OH)4 + H2O and its subsystem at 288.15 K and ambient pressure. (November 2020) - Zhao, Kaiyu; Sun, Kangrui; Guo, Yafei; Meng, Lingzong; Deng, Tianlong
Highlights: The system (Li2 B4 O5 (OH)4 + LiB5 O6 (OH)4 + H2 O) by isopiestic method was presented. Water activities and osmotic coefficients of this ternary system were firstly obtained. The Pitzer thermodynamic model of this ternary system was constructed. The calculated water activities agree well with the experimental values. Abstract: The isopiestic equilibria for the systems Li2 B4 O5 (OH)4 + H2 O, LiB5 O6 (OH)4 + H2 O and Li2 B4 O5 (OH)4 + LiB5 O6 (OH)4 + H2 O at 288.15 K and ambient pressure were measured by the isopiestic method using a modified gravimetric isopiestic apparatus. The water activities and osmotic coefficients were determined based on the sodium chloride standard reference solution. On the basis of Pitzer model, an extended Pitzer model was developed to describe the thermodynamic properties of the aqueous systems containing different forms of lithium borates, then the Pitzer single salt parameters β (0), β (1), β (2) and C ϕ for the binary systems Li2 B4 O5 (OH)4 + H2 O and (LiB5 O6 (OH)4 + H2 O and mixing ion-interaction parameters θ B 4 O 5 OH 4, B 5 O 6 OH 4 and ψ Li, B 4 O 5 OH 4, B 5 O 6 OH 4 for the ternary system Li2 B4 O5 (OH)4 + LiB5 O6 (OH)4 + H2 O were fitted with the experimental osmotic coefficients using the Fortran 97 program. Meanwhile, the water activities were calculated by the Pitzer parameters, and the good agreement between the calculated water activities and experimental results of this ternary system indicated that the Pitzer parameters obtained in this work were reliable.